EFEKTIVITAS TEHNIK ROUND ROBIN UNTUK MENINGKATKAN KECAKAPAN BERPIKIR KRITIS DALAM MENULIS PREFERENCE - Esti Nurul; Listyaning Sumardiyani; Sukma Nur Ardini; Sari Wulandari (Universitas Tidar, 2023)
Critical thinking skills are part of the 21st century skills that must be mastered by students. Whether writing skill is the main competency that should be mastered in learning English. One of the reasons for the lack of development of students' critical thinking skills in writing preference sentences is that their low enthusiasm for learning is caused by learning activities that are not give any other variation. This study aims to obtain findings related to the application of learning activities with the round robin technique, such as the increase in students' critical thinking skills in their writing preferences, by applying and observing how much effectiveness this type of learning has. This research is classified as quantitative research with the type of quasi-experimental research that conducts experiments through a pretest and posttest control group design with samples used by students of classes VII G and VII I at SMPN 21 Semarang. The research subjects were obtained using a random sampling technique, which was determined based on random choices. Essay tests are used as a tool to test critical thinking skills with preferred research material. The research results obtained based on the results of the significance test obtained an N-Gain percentage of 57.35%. This result is include to the quite effective category. In accordance with this results, it can be concluded that the use of round-robin type can improve critical thinking skills in writing preferences by class VII students of SMPN 21 Semarang effectively.